Incorporating the Spirit of Sandur into Grafito Akhudiats Work: A Review of Contemporary Music - Putri, Ratna; Hari Pramono, Koko; Wicahyo, Oki Dwi (Terob : Jurnal Pengkajian dan Penciptaan Seni, 2025)
Modern theatre is a pioneer that has shaped and impacted the performing arts. Currently, educational resources at both school and college levels frequently include content pertaining to modern theatre, contributing to the accessibility of information and expertise regarding this subject across numerous educational tiers. Within the robust and profound discourse surrounding contemporary theatrical materials, one finds the Sedhet Srepet studio in Bojonegoro, which distinctively integrates modern theatre with traditional theatre, specifically Sandur. Notably, while the Sedhet Srepet studio creates new theatre, it fundamentally employs a classic theatrical technique. Therefore, the researcher chose the performance piece titled Grafito for an in-depth examination concerning modern accompanying music. The analysis of music arises from the researcher's preliminary assumption that the musical accompaniment enhances the significance of the Grafito performance within the Sandur approach. Each musical scene encapsulates the atmosphere and effectively supports the actor's role. As a result, this study will employ a qualitative research methodology for analysis.